2019
DOI: 10.18632/aging.102094
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA FALEC inhibits proliferation and metastasis of tongue squamous cell carcinoma by epigenetically silencing ECM1 through EZH2

Abstract: Tongue squamous cell carcinoma (TSCC), the most common epithelial cancer identified in the oral cavity, has become one of the most common malignancies across the developing countries. Increasing evidence indicates that long non-coding RNAs (lncRNAs) serve as important regulators in cancer biology. The focally amplified long non-coding RNA in epithelial cancer (FALEC) was found downregulated in the tissues of tongue squamous cell carcinoma (TSCC) and was predicted to present a good prognosis by bioinformatics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…A change in lncRNA expression has been identified in a variety of human cancer types, including gastric cancer (11), thyroid cancer (12), hepatocellular carcinoma (13) and TScc (14). Regarding TScc, recent studies have indicated that numerous lncRNAs are abnormally expressed in this type of tumor and act as either tumor-suppressors or oncogenic RNAs (15,16). The abnormal expression of lncRNAs may contribute toward the malignancy of TScc by affecting a number of malignant characteristics (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…A change in lncRNA expression has been identified in a variety of human cancer types, including gastric cancer (11), thyroid cancer (12), hepatocellular carcinoma (13) and TScc (14). Regarding TScc, recent studies have indicated that numerous lncRNAs are abnormally expressed in this type of tumor and act as either tumor-suppressors or oncogenic RNAs (15,16). The abnormal expression of lncRNAs may contribute toward the malignancy of TScc by affecting a number of malignant characteristics (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, growing evidence has demonstrated that lncRNAs may also have essential roles in TSCC. For example, overexpression of the lncRNA FALEC represses malignant behaviors in TSCC (6). Upregulation of the lncRNA HOTTIP in TSCC patients indicates a poor clinical prognosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, long noncoding RNAs (lncRNAs) are RNA transcripts longer than 200 nucleotides and have no obvious protein-coding capacity. LncRNAs affect various aspects of biological processes in TSCC, including cell proliferation, tumorigenesis, survival, apoptosis, and migration [3] [4] [5] [6] . However, the underlying mechanisms have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple lncRNAs have been identified in TSCC. For example, upregulation of the lncRNA FALEC suppresses malignant behaviors in TSCC [6] . Overexpression of the lncRNA HOTTIP in TSCC patients indicates a poor clinical prognosis [5] .…”
Section: Introductionmentioning
confidence: 99%